Development of Interactive E-Modules Based on Problem-Based Learning (PBL) to Improve Students’ Problem-Solving Skills in Biotechnology Materials - Ermila Mahariyanti; Irwansah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study developed and evaluated a Problem-Based Learning (PBL)-based interactive e-module for biotechnology instruction, with a focus on improving students’ problem-solving skills. The module was designed around contextual biotechnology issues related to industry and health to support students in connecting biological concepts with real-world applications. The study employed a Research and Development approach using the 4D model (Define, Design, Develop, Disseminate). Participants consisted of 15 Grade XII science students in a small-scale trial and 30 Grade XII science students in a large-scale implementation. Feasibility results indicated that the e-module met “good” criteria based on expert and practitioner appraisal: material expert (76.67%), media expert (76.56%), biology teacher (75.00%), and peer reviewers (76.11%). Practicality results from the small-scale trial showed positive student responses, including usability (80.8%; good), display and presentation (81.0%; excellent), and material presentation (79.4%; good). Effectiveness findings showed a moderate improvement in problem-solving performance in the small-scale trial (N-gain = 0.46). In the large-scale implementation, paired-samples analysis indicated a significant difference between students’ performance before and after learning with the e-module (p = 0.029), suggesting improved outcomes following implementation. Overall, the findings support that the PBL-based interactive e-module is feasible, practical, and associated with improved student problem-solving performance in biotechnology learning.